The Collective Process: first impressions for the construction of a new procedural dogmatics - Alexandre Rocha Almeida de Moraes; Rafael de Oliveira Costa (Revista Brasileira de Direito Processual Penal, 2019)
As a result of the collectivization of litigations in the criminal sphere and of the lack of dialogue with the procedural protection, we are now facing a new branch of law, so-called Collective Criminal Procedure. It is an instrument used by the State to impose a criminal sanction on the perpetrator of the offense that violates collective rights, and is based on the respect of human rights and the effectiveness of the criminal system. The present article intends to problematize those that require the construction of a new model of procedural criminal dogmatics, whether inspired by the collective civil process or from the perspective of subsequent litigation, besides discussing the role of the Public Prosecution Service in its criminal activity.